Cellulose Binding Domains of a Phytophthora Cell Wall Protein Are Novel Pathogen-Associated Molecular Patterns - Gaulin, E.; Drame, N.; Lafitte, C.; Torto-Alalibo, T.; Martinez, Y.; Ameline-Torregrosa, C.; Khatib, M.; Khatib, M.; Villalba-Mateos, F.; Kamoun, S.; Mazars, C.; Dumas, B.; et al.
The cellulose binding elicitor lectin (CBEL)from Phytophthora parasitica nicotianae contains two cellulose binding domains (CBDs)belonging to the Carbohydrate Binding Module1 family, which is found almost exclusively in fungi. The mechanism by which CBEL is perceived by the host plant remains unknown. The role of CBDs in eliciting activity was investigated using modified versions of the protein produced in Escherichia coli or synthesized in planta through the potato virus X expression system. Recombinant CBEL produced by E. coli elicited necrotic lesions and defense gene expression when injected into tobacco (Nicotiana tabacum)leaves. CBEL production in planta induced necrosis. Site-directed mutagenesis on aromatic amino acid residues located within the CBDs as well as leaf infiltration assays using mutated and truncated recombinant proteins confirmed the importance of intact CBDs to induce defense responses. Tobacco and Arabidopsis thaliana leaf infiltration assays using synthetic peptides showed that the CBDs of CBEL are essential and sufficient to stimulate defense responses. Moreover, CBEL elicits a transient variation of cytosolic calcium levels in tobacco cells but not in protoplasts. These results define CBDs as a novel class of molecular patterns in oomycetes that are targeted by the innate immune system of plants and might act through interaction with the cell wall.